The Impact of Urbanization on the Socio-Economics of Communities in Ternate City - Hasim, Jainudin; Adjam, Syarifuddin; Samili, Asnita Ode; Yamin, Fahrun; Purwati, Endang; Robo, Tamrin (Peneliti.net, 2023)
The movement of people from villages to cities is influenced by several factors such as the desire to get a better job, the desire to continue their education to a higher level, the desire to get a higher salary, the existence of more complete health facilities in the city and the proliferation of entertainment facilities that can be one of the interesting factors in the city. It's just that this urbanization has the potential to have its own impacts on cities, for example, the increasing density of the population in cities causes the emergence of slum settlements and environmental damage